Stable coronary artery disease and left ventricular dysfunction: The role of revascularization. Issue 5 (14th July 2017) - Aksut, Baran; Starling, Randall; Kapadia, Samir
Abstract: The aim of this review is to present existing evidence of revascularization in patients with stable coronary artery disease (CAD) and left ventricular (LV) dysfunction. A literature review was performed for trials studying revascularization, via CABG or PCI, in patients with CAD and LV dysfunction. Pivotal, high‐quality trials have investigated revascularization with CABG in stable CAD and LV dysfunction. CASS demonstrated improved 10‐year survival in the surgical group compared to medically treated patients. While 56‐month follow‐up of the STICH trial found no statistically significant difference between CABG and medical therapy in patients with stable CAD and LV dysfunction, the long‐term follow‐up at 10 years (STICHES) demonstrated that CABG did significantly decrease death from any cause and all secondary outcomes. However, these pivotal trials have focused solely on surgical revascularization. Comparable studies regarding outcomes after contemporary PCI methods in this particular subset of patients are severely lacking. More recent studies have included very small numbers of patients with reduced EF. In conclusion, given advances in surgical and non‐invasive fields, studies investigating long‐term effects of PCI versus CABG, including combined hybrid revascularization techniques are warranted. This review sets the stage for a high‐quality randomized, controlled trial comparing revascularization with PCI versus CABG in patients with stable CAD and LV dysfunction.